PORTRAIT AS CATHARSIS - Anandi Rifki, Hikari
Everyone has their own problems. Humans are often faced with a new reality that is not in accordance with the reality they live in. When the change in reality occurs, various emotions often come overflowing together until they pile up and too heavy to deal with. Often when a person goes too far, he forgets what is the closest. In this case, focus on yourself. Communication with oneself can have a positive impact on a person's mental and physical condition. Departing from personal experiences and problems, the author raises his personal problems into the work of the final project. This final project describes the author's work coherently. Art, as a medium for expression, can be a way to communicate and reorganize an individual. That way every individual can accept the fact that every human being must have made a mistake in their whole life journey and that is a natural and beautiful thing.